Kuriančioji emocija ir demokratijos suvokimas H. Bergsono filosofijoje. - Aleksandravičius, Povilas (Problems / Problemos, 2021)
In this paper, the concept of creative emotion (émotion créatrice) and the understanding of democracy, which arises out of it, in the philosophy of Bergson is analysed. This specific emotion does not depend on an object's intellectual representation; therefore, Bergson refers to it as "supra-intellectual." Contrary to the usual "infra-intellectual" emotions, it is primary in regard of the mind and the will, and it comprises the fundamental matrix of creative acts of the human being. Creative emotion is one of the forms of the intuition of duration that is rooted in élan vital. It not only determines the essential changes in the fields of art, religion or science, but also re-configures the political rationality by revealing a deeper form of sociality. Thus, the presumed anti-sociality of the philosophy of Bergson is denied. In his last work, The Two Sources of Morality and Religion, Bergson shows how creative emotion transforms understanding of democracy and how it turns this political conception into a dynamic movement corresponding to the deep process of the human being and the whole reality.